Medición De Indicadores De Bienestar Animal (Awin) En Caballos Deportivo En La Escuela De Equitación San Rafael (2023)
The purpose of this project is to evaluate the animal welfare in 11 equines of the riding and polo school San Rafael by means of the protocol "Animal Welfare Indicators (AWIN)" and by means of a general clinical examination in order to highlight the positive aspects and make feedback to the place; at the same time to make a comparison with the reference population that evaluates this protocol; this in order to provide support to the existing legislation and promote the evaluation of animal welfare in equines of the different disciplines that are exercised in Colombia.